Green cities : urban growth and the environment - Kahn, Matthew E., 1966- (Brookings Institution Press, 2006)
Rapid urban growth and suburban sprawl have heightened concern in many quarters about sustainable development. Are economic growth and environmental health always mutually exclusive goals? Nearly everyone would choose to pursue both given the chance, but many believe that it would be overly optimisticperhaps naveto expect both.